Water mass characteristics and hydrodynamics at an inshore versus an offshore mid-Norwegian cold-water coral reef habitat - Büscher, Janina Vanessa; Juva, Katriina; Flögel, Sascha; Wisshak, Max; Rüggeberg, Andres; Riebesell, Ulf; Form, Armin Uwe (Frontiers in Marine Science, 2024)
Introduction Cold-water coral reefs form complex benthic habitats, supporting thousands of species. The broadscale environmental tolerances of reef-forming species such as Lophelia pertusa are well studied, but small-scale differences between different reef settings have received little attention so far. The controlling factors of thriving cold-water coral reefs and how these habitats differ in terms of framework extent, coral colony morphology, and associated fauna could reveal how these benthic ecosystems form and expand. Information on the natural range of environmental fluctuations could provide a better understanding of the resilience of such ecosystems towards environmental changes. Our study aimed to elaborate small-scale forces on local hydrodynamics and oceanographic parameters at two geographically close but contrasting reef sites in mid-Norway. Methods We investigated natural fluctuations and the seasonal variability of environmental conditions of an inshore and an offshore Lophelia-dominated reef over an annual cycle by time series monitoring of physical properties by benthic landers and water sampling for biogeochemical variables using CTD casts. Results and discussion The flow fields at the extensive reef on the offshore Sula Ridge and a bank reef at Nord-Leksa in a fjord-system differed regarding both short-term and seasonal levels. The inshore flow field was strong and tidally driven, whereas the offshore flow field was slower with large seasonal variability. The local flow regimes and the seasonal atmospheric forcing could explain the observed seasonality of the hydrographic variables and the observed inter-annual variability in biogeochemical variables. Comparison with a flow model showed that the natural short-term and seasonal variability are driven by small-scale forcing that is not represented in model analyses. These results suggest that local hydrodynamics together with sea-floor topography control the reef extent and the morphology of cold-water coral colonies.